Путешествия Гулливера: Роман / Дж. Свифт - Свифт Джонатан (Юлдузча, 1988)
4-5 Экземпляры: ф-3 (ретроконверсия) / Инвентарный номер: 30897 / Цена: 1.15 / Сис.шифр: Сб / Авт.знак: С 24 / ГРНТИ: 17.82 / ББК: 84(0)